Spatial Design and User Experience in Nepali Theaters: A Comparative Study of Architectural Layouts in Kathmandu and Pokhara - Pokharel, Rojina; Shrestha, Samriddhi; Shrestha, Sadichchha; Rana, Shreema (Journal of Himalaya College of Engineering, 2025)
The research explores the spatial layout of theaters in Kathmandu and Pokhara valley, centering on the needs and preferences of users—both performers and audiences. It examines how theater spaces interact with actors’ needs and audience expectations, employing a mixedmethod approach that combines literature review, surveys, and on-site observations. By analyzing existing challenges and opportunities, the research offers insights into designing theaters that respond directly to user requirements, enhancing performance quality, comfort, and engagement. The findings contribute to the enrichment of the two cities’ theatrical landscape by guiding the creation of user-centric spaces that foster creativity and artistic expression.